RADIOACTIVITY MEASUREMENT OF PRIMORDIAL RADIONUCLIDES IN AND DOSE EVALUATION FROM MARBLE AND GLAZED TILES USED AS COVERING BUILDING MATERIALS IN TURKEY - Turhan, Şeref; Varinlioğlu, A. (Radiation Protection Dosimetry (2012), Vol. 151, No. 3, pp. 546–555, 2012)
Measurements of the natural radioactivity arising from primordial radionuclides (226Ra, 232Th and 40K) in marble and glazed tile samples used covering building materials in Turkey were carried out by gamma-ray spectrometer with a high purity germanium detector. The mean activity concentrations of the 226Ra, 232Th and 40K in marble and glazed tile samples were found as 8.2, 5.5 and 58.1 Bq kg21 and 81.2, 65.4 and 450.1 Bq kg21, respectively. The radiation doses received by occupants of buildings in which the sample marble and glazed tiles might be used are estimated using measured activity concentrations of constituent primordial radionuclides and dose conversion factors evaluated by the European Commission from models of tile use. Results obtained are presented for each radionuclide, analysed and compared with relevant national and international legislation, guidance and report, and with the results obtained from other studies. Results show that the use of such decorative building materials in the construction of domestic homes or workplaces in Turkey is unlikely to lead to any significant radiation exposure to the occupants
Keywords: RADIOACTIVITY, PRIMORDIAL RADIONUCLIDES, GLAZED TILES